Greenhouse gas emission inventories from waste sector in China during 1949–2013 and its mitigation potential. (20th July 2017) - Lou, Ziyang; Cai, Bo-Feng; Zhu, Nanwen; Zhao, Youcai; Geng, Yong; Yu, Bao; Chen, Wei
Abstract: As an important anthropogenic greenhouse gas (GHG) emission source, GHG emission pattern from municipal solid waste (MSW) sector is unclear, which impairs the effective decision making for potential GHG reduction. The variations tendency of GHG inventories were studied from 1949 to 2013 in China on the basis of first order decay (FOD) method, and the total estimated GHG was found to be increased from 0.36 to 72.4 Mt CO2 -equiv in this work. Landfill was the main contributor for the GHG emissions, and the occupied percentage increased from 17% in 1979, to the peak value of 82% in 1999, and finally to 69.5% in 2013. The regional GHG division patterns were calculated every 5 years after 2003 due to the remarkable increase of MSW in past decades. East China was found to be the dominant region for GHG emissions, while the corresponding percentage decreased from 38.60% in 2003 to 30.75% in 2013. The percentage increased from 4.69% to 7.31%, as more MSW were landfilling in North West. The methane mitigation technologies, especially the soil cover and landfill gas collection-flaring, are the main contribution for CH4 reduction. The diversion alternatives for landfill are effective in the indirect GHG mitigation, and the reduction of MSW disposal is another critical part through the implementation of "pay-as-your-throw" and environmental protection tax. Graphical abstract: Variations of CO2 -equiv emission from MSW sector in China from 1949 to 2013. Highlights: GHG emission from MSW sector of 60 years was firstly estimated in China. Landfill was the main GHG contributor, and increased from 17% (1979) to 69.5% (2013). One third of GHG emission was from MSW in East China, with a range of 26.4–39.6%.